The brandon method in modelling the cavitation processing of aqueous media - Znak, Zenoviy; Sukhatskiy, Yuriy (Eastern-European Journal of Enterprise Technologies, 2016)
A 4-factor multiplicative mathematical model was built in order to find the best mode of cavitation processing of aqueous media, in which the value of heat energy released during cavitation is maximal. The model links the heat energy value with technological (inlet pressure in the cavitator) and design (nozzle diametre, the number of nozzles, the angle of attack jets) parametres. The adequacy of the derived regression equation is confirmed by the Fisher criterion (F<FT=0.203<1.51). The accuracy of the model has been assessed by the coefficient of determination and the mean relative error of approximation (eMRE=5.85 %). The analysis of the 4-factor multiplicative model allowed finding the optimal conditions for cavitation processing of liquid-phase media; they are as follows: inlet pressure – 0.54–0.6 MPa, nozzle diametre – 1.6 mm, the number of nozzles – 4–5, and the angle of attack jets – 144–170 degrees. It is found that, in comparison with the absence of air, the content of air of 2±0.25 % by the volume of an aqueous medium greatly intensifies the formation of the “flotation” layer (its height, dispersibility of bubbles, and gas saturation). The derived multifunctional dependence allows controlling the effectiveness of cavitation processing of aqueous media by means of changing the design parametres of cavitating parts.